2013
DOI: 10.1182/blood-2012-10-415000
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of carbohydrate determinants in regulating hemostasis: insights and opportunities

Abstract: Recent improvement in modern analytical technologies has stimulated an explosive growth in the study of glycobiology. In turn, this has lead to a richer understanding of the crucial role of N- and O-linked carbohydrates in dictating the properties of the proteins to which they are attached and, in particular, their centrality in the control of protein synthesis, longevity, and activity. Given their importance, it is unsurprising that both gross and subtle defects in glycosylation often contribute to human dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 96 publications
(64 reference statements)
5
72
0
Order By: Relevance
“…52,61 Nonetheless, it is interesting that in addition to influencing VWF clearance by macrophages, the N-linked glycans expressed within the A2 domain of VWF have also been shown to modulate susceptibility to proteolysis by ADAMTS13. 42,62 In particular, McKinnon et al showed that loss of the N-linked glycan at N1574 resulted in significantly enhanced VWF proteolysis by ADAMTS13. 42 Furthermore, differential scanning fluorimetry has confirmed that glycosylation at N1574 plays an important role in stabilization of the A2 domain against unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…52,61 Nonetheless, it is interesting that in addition to influencing VWF clearance by macrophages, the N-linked glycans expressed within the A2 domain of VWF have also been shown to modulate susceptibility to proteolysis by ADAMTS13. 42,62 In particular, McKinnon et al showed that loss of the N-linked glycan at N1574 resulted in significantly enhanced VWF proteolysis by ADAMTS13. 42 Furthermore, differential scanning fluorimetry has confirmed that glycosylation at N1574 plays an important role in stabilization of the A2 domain against unfolding.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in BHK manufacturing practices between Product B and Product D might have led to increased immunogenicity, 36 but the number of patients treated with Product B in both the RODIN study and in our cohort was too small for comparison with Product D. rFVIII molecules produced by BHK and CHO cells differ in several respects, such as the degree of tyrosine residue sulphation and type of glycosylation. 37 The presence of specific glycan chains might affect dendritic cell uptake and thereby modify rFVIII immunogenicity. 38 The amino acid sequence of the BHK rFVIII products (B and D) corresponds to the most frequent haplotype (H1) in the white population.…”
Section: Possible Biological Explanations and Implicationsmentioning
confidence: 99%
“…Within the hemostatic system, the presence of glycans on individual proteins has been demonstrated to alter expression, clearance, and catalytic activity. 15 O-glycans on von Willebrand factor (VWF) have been associated with changes in VWF plasma concentration, 16 platelet binding, 17 and response to shear stress. 18 O-glycosylation is also required for P-selectin-dependent leukocyte rolling, 19,20 and O-glycosylation of platelet glycoprotein Ib a (GP1BA) is important for binding to VWF.…”
Section: Introductionmentioning
confidence: 99%